Android application for dementia care patient - Ong, Jordan Zhi Rong (2016)
The rapid ageing population around the world has resulted in a significant increase in the number of people suffering from dementia, and the number is projected to be doubled or tripled in the next few decades. Therefore, there is a need for countries to be well equipped with the right technology and knowledge to assist patients that suffer from dementia. This project aims to develop an Android Application for the healthcare centers. This application will be used to help patients stimulate their cognition and exercise their mental health. Research has shown that these games will help slow down the symptoms of dementia. The application will help patient to improve on their hand-eye coordination. Patients are required to click on images that will randomly appear on the screen. Scores and movement logs will then be recorded and send to a database server. The gathered data will then be used by healthcare professionals and caregivers to monitor the patient’s health progress. The author emphasis on the consistency of coding and the flexibility to ensure that future FYP student can easily maintain and further develop the application to better serve the needs of the healthcare centers.